2017
DOI: 10.15625/0866-708x/55/2/8578
|View full text |Cite
|
Sign up to set email alerts
|

Ảnh Hưởng Của Việc Thay Thế Một Phần Nitrit Bằng Bột Hạt Điều Màu Đến Tính Chất Lý Hóa Của Xúc Xích Thịt Heo

Abstract: This study investigated the effect of powder from the outer layer of annatto (Bixa orellana L.) seeds on the physicochemical properties and the antioxidant and antimicrobial activities of pork sausages. In fact, six treatments of pork sausage were made including four different concentrations of annatto seed powder as follows: 0.025, 0.05, 0.1, 0.2 % (T1, T2, T3, and T4, respectively), and 100 % with nitrite (150 ppm, REF); and control (CTL) without nitrite. The Hunter color values of pork sausages were affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…The authors noted that the highest quantities of the plant extracts showed the greatest inhibitory effect toward the formation of TBARS. Similar observations were recorded by van Cuong and Thoa [77]. They added the seed powder of B. orellana (L) to the product, which contributed to the reduction of primary and secondary lipid oxidation products to an extent similar to that achieved in the control sample (150 ppm nitrite) [77].…”
Section: Antioxidant Propertiessupporting
confidence: 77%
See 3 more Smart Citations
“…The authors noted that the highest quantities of the plant extracts showed the greatest inhibitory effect toward the formation of TBARS. Similar observations were recorded by van Cuong and Thoa [77]. They added the seed powder of B. orellana (L) to the product, which contributed to the reduction of primary and secondary lipid oxidation products to an extent similar to that achieved in the control sample (150 ppm nitrite) [77].…”
Section: Antioxidant Propertiessupporting
confidence: 77%
“…Similar observations were recorded by van Cuong and Thoa [77]. They added the seed powder of B. orellana (L) to the product, which contributed to the reduction of primary and secondary lipid oxidation products to an extent similar to that achieved in the control sample (150 ppm nitrite) [77]. Another study demonstrated that the antioxidant capacity of the product increases with an increasing quantity of plant extract.…”
Section: Antioxidant Propertiessupporting
confidence: 77%
See 2 more Smart Citations